Stipa capillata L. (Poaceae) на Київському плато: еколого-ценотичні умови місцезростань, стан і структура природних та інтродукційних ценопопуляцій - Gritsenko, V.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
Ecological and coenotical conditions of habitats, state and structure of natural and introduced cenopopulations of the rare species of the flora of Ukraine – Stipa capillata L. (Poaceae) in the terrain of Kyiv plateau are characterized. The analysis of efficiency of protection of the Stipa capillata ex situ is given.